Deciphering the role of materia medica in the primary healthcare needs and managing livestock diseases among the Batswana in South Africa - John A. Asong; Madeleen Struwig; Morris M. Lebekwa; Adeyemi O. Aremu (Phytomedicine Plus)
Background: The Batswana descended mainly from Bantu-speaking tribes and regarded as an indigenous group in Southern Africa. Among this native group, medicinal plants play key roles for their primary healthcare needs and general well-being as well as managing livestock diseases. Purpose: This study documented the ethnobotanical knowledge of medicinal plants used by the Batswana for managing their healthcare needs and livestock diseases in Mahikeng Local Municipality, South Africa. Methods: A total of 128 participants comprising traditional healers and community members from 28 of the 35 wards in Mahikeng Local Municipality were interviewed, using semi-structured questionnaires. Ethnobotanical data including the local names, plant parts used, method of preparation and administration of the identified plants were documented. The data was analysed using relative frequency of citation (RFC) and use-value (UV). Results: We recorded 100 plants representing 40 families used for alleviating 74 health problems affecting humans and livestock. The commonly treated health issues were dermatological (39 %), gastrointestinal (18 %) and respiratory (16 %) diseases. A total of 34 plants were used for treating diseases in humans and livestock. Based on the RFC values, the dominant plants were Hypoxis hemerocallidea Fisch.C. A Mey & Ave (0.73), Entada elephantina (Burch.) S.A.O’Donell & G.P. Lewis (0.66), Helichrysum paronychioides DC. Humbert (0.63) and Drimia sanguinea (Schinz) Jessop (0.63). In terms of UV, the top-ranked plants were Hypoxis hemerocallidea (0.18) and Entada elephantina (0.13). The dominant parts used for making herbal recipes were the leaves (27 %), roots (24 %) and whole plants (22 %). Conclusion: The high number of plants recorded highlights the value and dependence on botanicals in folklore medicine among the Batswana. The current endeavour was vital towards preventing the erosion of important traditional knowledge and applications for the benefit of the present and future generations as well as potential downstream applications in the pharmaceutical and nutraceutical industries.